2008
DOI: 10.1002/mmce.20354
|View full text |Cite
|
Sign up to set email alerts
|

A 2D design and modeling of micro strip structures on inhomogeneous substrate

Abstract: The wave concept iterative process method (WCIP) is presented for full wave investigation of a microwave structure on inhomogeneous substrate. These structures can be exploited to achieve a high performance due to their versatility, which can reduce manufacturing cost, size, and weight. Using the spectral operator in the WCIP method permits to resolve this inhomogeneous problem. The use of the spectral operator keeps the advantages of the 2D mesh of the circuit plan. Two different examples are studied; the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The latter is based on the method of the moments. This method is very interesting since it is employed by the majority of the most important editors of electromagnetic simulators [9]. An evaluation of the number of fundamental operations in the iterative method (F.W.C.I.P) and the method of moments showed that starting from a certain density of grid of the study structure (Figure 3), the economy in a number of operations, therefore in computing times, is then considerable and widely justices the use of the F.W.C.I.P.…”
Section: Study Of the Numerical Complexity And The Convergence Of The Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is based on the method of the moments. This method is very interesting since it is employed by the majority of the most important editors of electromagnetic simulators [9]. An evaluation of the number of fundamental operations in the iterative method (F.W.C.I.P) and the method of moments showed that starting from a certain density of grid of the study structure (Figure 3), the economy in a number of operations, therefore in computing times, is then considerable and widely justices the use of the F.W.C.I.P.…”
Section: Study Of the Numerical Complexity And The Convergence Of The Methodsmentioning
confidence: 99%
“…Then there are described extensively in [9] and [10]. The small guide is a 2D periodic guide, and the bases functions are exponential.…”
Section: Reflection Operator Determinationmentioning
confidence: 99%
“…This is proven in several research works. [1][2][3][4][5] The iterative method is absolutely convergent, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but in some cases of electronic circuits the number of iterations required to reach a stable value is relatively high. The numerical complexity of the studied circuit is related to the number of cells describing the structure requiring a fine mesh.…”
Section: Introductionmentioning
confidence: 99%
“…The wave iterative method (WCIP) (Wave Concept Iterative Process) is an integral method based on wave concept for solving problems of electromagnetic diffraction and analysis of planar circuits [1][2][3][4][5][6][7][8]. It is based on the manipulation of incident and reflected waves instead of electromagnetic field [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the manipulation of incident and reflected waves instead of electromagnetic field [1][2][3][4]. It is mainly based on two equations, one in the spatial domain and the other in the spectral domain.…”
Section: Introductionmentioning
confidence: 99%